2019
DOI: 10.1002/qj.3430
|View full text |Cite
|
Sign up to set email alerts
|

The intensity and motion of hybrid cyclones in the Australian region in a composite potential vorticity framework

Abstract: Hybrid cyclones (HCs) in the Australian region typically reach their peak intensity in an amplified flow comprising upper-tropospheric ridges upstream and downstream of the cyclone and a north-south elongated trough. Nonetheless, there is considerable case-to-case variability. Taking a composite viewpoint, the present study investigates how such variations in the upper-tropospheric potential vorticity (PV) anomalies affect the subsequent intensity and motion of HCs in the Australian region. First, cyclones are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The relative contribution of diabatic processes to ETC intensification can be quantified via the pressure tendency equation [27], the omega equation [28,29], or the Zwack-Okossi equation [30]. Another perspective on the influence of LH on cyclones can be obtained from the potential vorticity (PV) framework [31]: diabatic PV generation associated with LH in clouds leads to the formation of a cyclonic PV anomaly in the lower troposphere that contributes to the cyclonic circulation [25,26,[32][33][34]. More recent climatological studies have used this lower-tropospheric PVanomaly as a measure of the relevance of diabatic processes for ETCs in different regions [35] and of different intensities [36,37], indicating that such lower-tropospheric PVanomalies are dominant factors in the development of many intense ETCs [37].…”
Section: Theoretical Mechanisms For Future Changes In Etcsmentioning
confidence: 99%
“…The relative contribution of diabatic processes to ETC intensification can be quantified via the pressure tendency equation [27], the omega equation [28,29], or the Zwack-Okossi equation [30]. Another perspective on the influence of LH on cyclones can be obtained from the potential vorticity (PV) framework [31]: diabatic PV generation associated with LH in clouds leads to the formation of a cyclonic PV anomaly in the lower troposphere that contributes to the cyclonic circulation [25,26,[32][33][34]. More recent climatological studies have used this lower-tropospheric PVanomaly as a measure of the relevance of diabatic processes for ETCs in different regions [35] and of different intensities [36,37], indicating that such lower-tropospheric PVanomalies are dominant factors in the development of many intense ETCs [37].…”
Section: Theoretical Mechanisms For Future Changes In Etcsmentioning
confidence: 99%
“…Its structure is less clear, although it points to a weaker downstream ridge in events with a strongly positively tilted trough. The information of this EOF analysis is used in a companion paper (Quinting et al ) to separate all HCs into four clusters, and to address the question how the upper‐level PV structure affects the intensity and motion of HCs.…”
Section: Synoptic Climatologymentioning
confidence: 99%
“…However, this method focused on point data and did not assess or group by track characteristics. Previous studies in Australia (Quinting, Reeder, & Catto, 2019b; Ramsay et al, 2012) have demonstrated how advantageous cluster analysis using tracks has been in investigating spatial and temporal trends of tropical cyclone (TC) events, a field of research that has not been applied in‐depth for ECC events.…”
Section: Introductionmentioning
confidence: 99%